Stepping into Islamic environmental sustainability in Indonesia: developing a framework for balancing economic growth, renewable energy, and carbon emissions - Qoyum, Abdul; Prasojo, Prasojo; Mohd Thas Thaker, Hassanudin; Hosen, Mosharrof; Hasanah, Imas (UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
The growing threat of climate change and environmental degradation has intensified interest in understanding the role of renewable energy in promoting economic growth while reducing carbon dioxide (CO₂) emissions. This study examines the interrelationships among political risk, financial risk, technological innovation, renewable energy consumption, environmental pollution, and CO₂ emissions in the Indonesian context. Secondary data were obtained from reputable sources, including Bloomberg and the World Development Indicators (WDI). To ensure robust empirical analysis, this study employs Wavelet analysis and the Autoregressive Distributed Lag (ARDL) approach to capture both short-run and long-run dynamics. The empirical findings reveal the existence of a long-run cointegrating relationship among the studied variables, indicating that renewable energy, financial conditions, and environmental factors move together toward long-term equilibrium. The long-run results show that financial conditions have a positive and statistically significant impact on carbon emissions, suggesting that financial expansion may intensify environmental pressures if not aligned with sustainable policies. These findings provide important policy implications, highlighting the need to strengthen green finance mechanisms, support renewable energy investments, and promote clean technological innovation to achieve sustainable economic development. The study offers valuable insights for policymakers in designing effective strategies to balance economic growth with environmental sustainability in Indonesia